Photochemical aging of volatile organic compounds in the Los Angeles basin: Weekday‐weekend effect. Issue 10 (29th May 2013) - Warneke, Carsten; de Gouw, Joost A.; Edwards, Peter M.; Holloway, John S.; Gilman, Jessica B.; Kuster, William C.; Graus, Martin; Atlas, Elliot; Blake, Don; Gentner, Drew R.; Goldstein, Allen H.; Harley, Robert A.; et al.
Abstract: [1] During the CalNex (California Research at the Nexus of Air Quality and Climate Change) field study in May–June 2010, measurements of volatile organic compounds (VOCs) were performed in the Los Angeles (LA) basin onboard a NOAA research aircraft and at a ground site located in Pasadena. A weekday‐weekend effect in ozone, caused by lower NO x emissions due to reduced diesel truck traffic in the weekends, has been previously observed in Los Angeles and other cities. Measurements in the Caldecott tunnel show that emission ratios of VOCs do not vary with the day of the week, but measurements during CalNex2010 show a VOC weekday‐weekend effect through faster photochemical processing at lower ambient NO x mixing ratios. Ambient VOC enhancement ratios of long‐lived species such as benzene are the same between weekdays and weekends, whereas enhancement ratios of short‐lived species, such as trimethyl benzene, are up to a factor of three lower on weekends. Based upon the observed differences in VOC enhancement ratios to CO, we determine that photochemical processing was on average 65%–75% faster on weekends during CalNex2010, which indicates that ambient OH radical concentrations were larger by this factor causing the observed change in VOC composition. A box model calculation based on the Master Chemical Mechanism was used to verify the increase in photochemical processing in the weekends. Key Points: Spatial and temporal photochemical processing in Los Angeles VOC weekday‐weekend effect Faster photochemistry in weekends